A method for producing a waterproof and moisture-permeable film

CN122978431APending Publication Date: 2026-10-27WANHUA CHEM GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610953435.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但其制备方法比较繁琐复杂,需要添加二异氰酸酯进行扩链,且合成的尼龙弹性体不具备防水透湿的功能

Benefits of technology

[0034]本发明的积极效果在于:通过结构设计,利用异氰酸酯及聚醚多元醇,将与尼龙相容性较差的PDMS成功引入尼龙主体结构中,然后利用利用温控相变诱导的硅氧烷软段表面富集机制,对尼龙弹性体进行梯度升温退火处理,得到防水性能更优的透湿膜,解决了现有尼龙弹性体体系在服装领域应用受限的问题。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a preparation method of a waterproof and moisture-permeable film. The preparation method comprises the following steps: S1, step-by-step mixing and reaction of polyether polyol, isocyanate and polydimethylsiloxane to prepare a polydimethylsiloxane-terminated triblock polyether soft segment; S2, preparation of a double-end carboxyl-terminated nylon hard segment by using a polyamide monomer and a long carbon chain dibasic acid; S3, melt polymerization of the polyether soft segment in S1 and the nylon hard segment in S2 to obtain a nylon elastomer; and S4, annealing treatment of the nylon elastomer after being processed into a film under different temperature gradients. The preparation method solves the problem that the polydimethylsiloxane and the nylon are greatly different in polarity and are difficult to be introduced due to serious phase separation, and the structure of the nylon elastomer is designed, so that the target material with more firm phase region combination and better waterproof and moisture-permeable effect is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermoplastic elastomer materials, and specifically relates to a method for preparing a waterproof and breathable membrane. Background Technology

[0002] Nylon elastomers are a type of block copolymer that combines the properties of rubber and thermoplastic resin. They exhibit rubber-like characteristics at room temperature, but can melt and plasticize at high temperatures. Different blocks provide different properties: hard segments act as physical crosslinking points to provide the required strength, while soft segments provide the material's toughness. Thermoplastic nylon elastomers are characterized by high tensile strength, high resilience, high low-temperature impact strength, excellent flexural strength, good abrasion resistance, and ease of processing and molding. They are currently widely used in sports footwear, outdoor clothing, medical supplies, and electronic equipment.

[0003] Most outdoor clothing uses a laminated structure, with the most crucial core layer being an extremely thin waterproof and breathable membrane. The performance of this membrane determines the overall performance of the garment. For a long time, Gore-Tex (expanded polytetrafluoroethylene) has been considered the representative material due to its excellent hydrophobicity, while nylon elastomers, with their hydrophilic and non-porous properties, have been widely used in the waterproof and breathable field and have seen rapid development in recent years. Their main mechanism involves the thermal motion of hydrophilic segments in the molecular structure providing intermolecular gaps for moisture to pass through, while water molecules cannot. Furthermore, to achieve even better waterproof performance, most manufacturers also apply a Teflon coating to the outermost layer of fabric.

[0004] As research has shown that PFAS (per- and polyfluoroalkyl substances) pose a threat to human health, potentially affecting immune system function, many countries have implemented "fluorine bans." Due to the gradual implementation of these bans, the use of Teflon coatings and Gore-Tex membranes will decrease in the future market, leading to a further decline in the waterproof performance of fabrics. Since nylon elastomers serve as the core layer, if moisture penetrates the outer layer and enters the middle layer, a series of problems will arise after the nylon elastomer membrane absorbs water. First, the moisture-permeable membrane expands after absorbing water, causing changes in its dimensions and resulting in overall fabric deformation. Second, the weight of the moisture-permeable membrane increases after absorbing water, further increasing the overall weight of the garment and negating the lightweight and thin advantages of a waterproof jacket. Most importantly, a water film forms on the surface of the moisture-permeable membrane after absorption, preventing the rapid adsorption and diffusion of water vapor in the environment, significantly reducing the membrane's moisture permeability. These problems limit the application of nylon elastomers in the clothing industry.

[0005] Patent CN113444243A describes the preparation of a polyether-organic silicone composite nylon elastomer material. The process involves physically blending polydimethylsiloxane and polybutanediol, then introducing the blend into a nylon 66 salt solution for polymerization to obtain the nylon elastomer. The main purpose is to increase the toughness and flexibility of conventional nylon elastomers. However, the blending of polyether and polydimethylsiloxane is only a simple physical blend, and polydimethylsiloxane has poor compatibility with nylon. Therefore, there is a risk of phase separation after polymerization, and the problem of surface water absorption in the prepared composite nylon elastomer remains unresolved.

[0006] Patent CN103910845B describes the preparation of a nylon elastomer material based on a polyamide-polysiloxane multiblock copolymer. The process involves isocyanate-terminated polysiloxane, followed by reaction with carboxyl-terminated polyamide and diisocyanate polymerization to obtain the multiblock nylon elastomer material. However, this preparation method is relatively cumbersome and complex, requiring the addition of diisocyanate for chain extension, and the synthesized nylon elastomer lacks waterproof and breathable properties.

[0007] In summary, a nylon elastomer material is needed that not only allows for normal moisture permeability but also possesses waterproof properties, and can even achieve waterproofing without a lamination structure, ultimately achieving surface waterproofing while maintaining moisture permeability within the material itself. Summary of the Invention

[0008] The purpose of this invention is to provide a method for preparing a waterproof and breathable membrane. This invention pre-links PDMS with a polyether polyol using isocyanate, with the PDMS portion "suspended" within the soft segments, maintaining good compatibility with the nylon hard segments and preventing macroscopic phase separation. Long-chain dicarboxylic acids are used to end-cap the long-chain nylon, further reducing the water absorption rate of the target material. A temperature-controlled phase transition-induced enrichment mechanism of siloxane soft segments is utilized to perform gradient-temperature annealing of the nylon elastomer, resulting in moderate microphase separation, promoting siloxane enrichment on the surface, reducing the soft / hard segment interfacial energy, achieving a waterproof effect, and ultimately realizing the design goal of a hydrophobic surface and breathable bulk.

[0009] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0010] A method for preparing a waterproof and breathable membrane includes the following steps:

[0011] S1: Polyether polyol, isocyanate and polydimethylsiloxane PDMS are mixed and reacted stepwise to prepare polydimethylsiloxane-terminated triblock polyether soft segments.

[0012] S2: Nylon hard segments with double-ended carboxyl groups were prepared by polymerizing polyamide monomers with long-chain dicarboxylic acids as end-capping agents;

[0013] S3: Melt polymerize the polyether soft segment of S1 with the nylon hard segment of S2 to obtain a nylon elastomer;

[0014] S4: After the nylon elastomer is processed into a film, it is annealed under different temperature gradients, held at the temperature for a certain time, and then slowly cooled to room temperature.

[0015] In this invention, the polyether polyol in S1 is one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), and polytetramethylene ether glycol (PTMG).

[0016] In this invention, the number-average molecular weight of the polyether polyol is 500-5000 g / mol, preferably 1000-2000 g / mol.

[0017] In this invention, the polydimethylsiloxane in S1 is a hydroxyl-terminated polydimethylsiloxane with a number-average molecular weight of 500-5000 g / mol, preferably 1000-3000 g / mol.

[0018] In this invention, the isocyanate in S1 is one or more of hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,5-toluene diisocyanate, 2,6-toluene diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate, and 1,5-naphthalene diisocyanate. Preferably, it is one or more of hexamethylene diisocyanate (HDI), 4,4'-diphenylmethane diisocyanate (MDI), and isophorone diisocyanate (IPDI).

[0019] In this invention, step S1 includes the following steps:

[0020] S1-1: Preparation of diisocyanate-terminated blocks by reacting polyether polyols with isocyanates.

[0021] S1-2: The reaction of diisocyanate-terminated blocks with PDMS.

[0022] In S1-1, the molar ratio of polyether polyol to isocyanate is (1:2)-(1:2.05), preferably (1:2)-(1:2.02); the reaction temperature is 80℃ and the reaction time is 3h.

[0023] In S1-2, the molar ratio of the diisocyanate-terminated block to PDMS is (2:2)-(2:2.05), preferably (2:2)-(2:2.02); the reaction temperature is 80℃ and the reaction time is 3h.

[0024] In this invention, the end-capping agent S2 is a long-chain dicarboxylic acid with the general formula HOOC-(CH2)n-COOH, where n=8-16, preferably sebacic acid, dodecanoic acid, or tetradecanoic acid.

[0025] In this invention, the polyamide monomer in S2 is selected from one or more of diamines and diacids, lactams or ω-aminocarboxylic acids.

[0026] In this invention, the diamine is selected from one or more of hexanediamine, decanediamine, dodecanediamine, tridecanediamine, and tetradecanediamine, preferably one or more of hexanediamine, decanediamine, and dodecanediamine.

[0027] As a preferred embodiment, in this invention, the dicarboxylic acid is selected from one or more of sebacic acid, dodecanoic acid, tridecanoic acid, and tetradecanoic acid. Sebacic acid and one or more of dodecanoic acid are preferred.

[0028] In this invention, the lactam is selected from dodecyl lactam, and the ω-aminocarboxylic acid is selected from undecyl amino acids.

[0029] As a preferred embodiment, in this invention, the nylon hard segment in S2 is selected from one or more of PA610, PA612, PA1010, PA1012, PA11, PA12, PA1212, PA1313, and PA1414, with PA612, PA1010, PA1012, PA12, and PA1212 being preferred.

[0030] In this invention, the nylon hard segment number-average molecular weight of the nylon in S2 is 500-8000 g / mol, preferably 1000-3000 g / mol.

[0031] In this invention, in step S2, the polymerization temperature is 220℃-320℃ and the polymerization time is 2-8h, with the preferred polymerization temperature being 260-300℃ and the polymerization time being 3-6h.

[0032] In this invention, in step S3, the melt polymerization temperature is 220-280℃ and the time is 3-10h, preferably 230℃-260℃ and 3-8h.

[0033] In this invention, the annealing in step S4 includes the following steps: a first gradient of slowly increasing the temperature from room temperature to 50°C, the main purpose of which is to exceed the glass transition temperature of the nylon elastomer and promote molecular chain movement; a second gradient of 50°C-80°C, held for 2-8 hours, the main purpose of which is to allow the molecular chains to acquire initial mobility, begin to eliminate internal stress and begin migration; a third gradient of 80°C-100°C, held for 2-8 hours, the main purpose of which is to allow the PDMS to obtain sufficient migration heat energy; and a fourth gradient of 100°C-130°C, held for 2-8 hours, and slowly cooled to room temperature, the main purpose of which is to provide the PDMS with sufficient kinetic energy to complete surface enrichment and alignment.

[0034] The positive effects of this invention are as follows: through structural design, PDMS, which has poor compatibility with nylon, is successfully introduced into the main structure of nylon using isocyanate and polyether polyol. Then, by utilizing the surface enrichment mechanism of siloxane soft segments induced by temperature-controlled phase change, the nylon elastomer is subjected to gradient temperature annealing treatment to obtain a breathable membrane with better waterproof performance, thus solving the problem of limited application of existing nylon elastomer systems in the clothing field. Detailed Implementation

[0035] To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0037] The following test methods are used in various embodiments of the present invention:

[0038] (1) Si / C atomic ratio: The final material is cut into a block sample of about 1cm*1cm, ensuring that the test surface is flat, free of fingerprints and dust. It is fixed on the XPS sample stage using double-sided conductive tape (carbon tape or copper tape) and scanned to obtain the Si / C atomic ratio.

[0039] (2) Moisture permeability: According to JIS L1099B1 standard, the final material is prepared as a 0.01 mm thick film, fixed on a moisture permeability cup containing desiccant, and moisture permeability test is performed.

[0040] (3) Hydrostatic pressure: According to GBT4744-2013 standard, the final material is cut into a 10cm*10cm film, and then the sample is placed face down in contact with the water surface to remove the air between the sample and the water surface. The cap is tightened, and distilled water at 20±2℃ or 27±2℃ is used to conduct the hydrostatic pressure test with a pressure increase rate of 6.0±0.3kPa / min.

[0041] Example 1

[0042] (1) Add 500g PTMG-1000 and 168.2g HDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 1000g PDMS-1000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0043] (2) 645.8g hexamethylenediamine, 1123.9g sebacic acid, 230.3g dodecanoic acid and 200g water were added to the reaction vessel, heated to 280℃, and polymerized for 5h to obtain double-ended carboxyl-terminated nylon hard segments.

[0044] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 250°C, and polymerize for 6 hours to obtain nylon elastomer;

[0045] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 5 hours; the third gradient is heated to 100°C and held for 2 hours; the fourth gradient is heated to 130°C and held for 3 hours, and then slowly cooled to room temperature to obtain the target material 1.

[0046] Example 2

[0047] (1) Add 500g PPG-1000 and 251.6g MDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 2030g PDMS-2000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0048] (2) 1197.4g of decanediamine, 1600.4g of dodecanoic acid, 202.3g of sebacic acid and 300g of water were added to the reaction vessel, heated to 260℃ and polymerized for 4h to obtain double-ended carboxyl-terminated nylon hard segments.

[0049] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 260°C, and polymerize for 3 hours to obtain nylon elastomer;

[0050] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 2 hours; the third gradient is heated to 100°C and held for 6 hours; the fourth gradient is heated to 130°C and held for 2 hours, and then slowly cooled to room temperature to obtain the target material 2.

[0051] Example 3

[0052] (1) Add 500g PEG-2000 and 111.1g IPDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 502.5g PDMS-1000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0053] (2) Add 398.9g dodecyl lactam, 101.1g sebacic acid and 100g water to the reaction vessel, heat to 290℃, and polymerize for 3h to obtain double-ended carboxyl-terminated nylon hard segments;

[0054] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 240°C, and polymerize for 5 hours to obtain nylon elastomer;

[0055] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 6 hours; the third gradient is heated to 100°C and held for 8 hours; the fourth gradient is heated to 130°C and held for 6 hours, and then slowly cooled to room temperature to obtain the target material 3.

[0056] Example 4

[0057] (1) Add 500g PEG-1000 and 169.9g HDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 3030g PDMS-3000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0058] (2) 1275.5g dodecanodiamine, 1466.1g dodecanodicarboxylic acid, 258.4g tetradecanodicarboxylic acid and 300g were added to the reaction vessel, heated to 300℃ and polymerized for 6h to obtain double-ended carboxyl-terminated nylon hard segments.

[0059] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 230°C, and polymerize for 8 hours to obtain nylon elastomer;

[0060] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 8 hours; the third gradient is heated to 100°C and held for 4 hours; the fourth gradient is heated to 130°C and held for 8 hours, and then slowly cooled to room temperature to obtain the target material 4.

[0061] Comparative Example 1

[0062] Compared with Example 1, conventional polyether soft segments are directly reacted with nylon hard segments to prepare nylon elastomers.

[0063] (1) 645.8g hexamethylenediamine, 1123.9g sebacic acid, 230.3g dodecanoic acid, 115.2g PTMG-1000 and 200g water were added to the reaction vessel, heated to 280℃ and polymerized for 5h to obtain nylon elastomer;

[0064] (2) The nylon elastomer obtained in step (1) was processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient was slowly heated from room temperature to 50°C; the second gradient was heated to 80°C and held for 5 h; the third gradient was heated to 100°C and held for 2 h; the fourth gradient was heated to 130°C and held for 3 h, and then slowly cooled to room temperature to obtain comparative material 1-1.

[0065] Comparative Example 2

[0066] Compared with Example 2, the difference is that no gradient heating post-treatment is performed.

[0067] (1) Add 500g PPG-1000 and 251.6g MDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 2030g PDMS-2000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0068] (2) 1197.4g of decanediamine, 1600.4g of dodecanoic acid, 202.3g of sebacic acid and 300g of water were added to the reaction vessel, heated to 260℃ and polymerized for 4h to obtain double-ended carboxyl-terminated nylon hard segments.

[0069] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 260°C, and polymerize for 3 hours to obtain comparative material 2-2.

[0070] Comparative Example 3

[0071] Compared with Example 3, the difference is that the third gradient heating post-treatment is not performed.

[0072] (1) Add 500g PEG-2000 and 111.1g IPDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 502.5g PDMS-1000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0073] (2) Add 398.9g dodecyl lactam, 101.1g sebacic acid and 100g water to the reaction vessel, heat to 290℃, and polymerize for 3h to obtain double-ended carboxyl-terminated nylon hard segments;

[0074] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 240°C, and polymerize for 5 hours to obtain nylon elastomer;

[0075] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 6 hours; then the temperature is directly increased from 80°C to 130°C, held for 6 hours and then slowly cooled to room temperature to obtain comparative material 3-3.

[0076] Comparative Example 4

[0077] Compared with Example 4, the difference is that the fourth gradient heating post-treatment is not performed.

[0078] (1) Add 500g PEG-1000 and 169.9g HDI to the polymerization reactor, raise the temperature to 80℃, react for 3h, then add 3030g PDMS-3000 and continue to react for 3h to obtain triblock polyether soft segments with dihydroxy polydimethylsiloxane end capping.

[0079] (2) 1275.5g dodecanodiamine, 1466.1g dodecanodicarboxylic acid, 258.4g tetradecanodicarboxylic acid and 300g were added to the reaction vessel, heated to 300℃ and polymerized for 6h to obtain double-ended carboxyl-terminated nylon hard segments.

[0080] (3) Add the product from step (1) to the nylon hard segment obtained in step (2), heat to 230°C, and polymerize for 8 hours to obtain nylon elastomer;

[0081] (4) The nylon elastomer obtained in step (3) is processed into a 0.01 mm film and subjected to gradient heating annealing. The first gradient is slowly heated from room temperature to 50°C; the second gradient is heated to 80°C and held for 8 hours; the third gradient is heated to 100°C and held for 4 hours before being slowly cooled to room temperature to obtain comparative material 4-4.

[0082] The Si / C atomic ratio, moisture permeability and hydrostatic pressure of the materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1 below.

[0083] Table 1 Sample Test Data

[0084] Test Project Test Standards Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Si / C atomic ratio / 0.22 0.28 0.26 0.35 0.02 0.08 0.14 0.10 Daily standard moisture permeability (g / m2·24h) JISL1099B1 87645 102548 150377 125663 26514 35126 47983 37651 Hydrostatic pressure (mmH2O) GBT4744-2013 9300 11000 16500 14700 5200 6600 7200 5700

[0085] As shown in Table 1, this invention introduces PDMS into nylon elastomer in a block form to prepare a waterproof and breathable membrane with excellent performance. The hydrostatic pressure is increased to 9000-16000 mmH2O, and the moisture permeability can reach 87000-150000 g / m². 2 ·24h.

[0086] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a waterproof and breathable membrane, comprising the following steps: S1: The polyether polyol, isocyanate and polydimethylsiloxane are mixed and reacted stepwise to prepare polydimethylsiloxane-terminated triblock polyether soft segments. S2: Nylon hard segments with double-ended carboxyl groups were prepared by polymerizing polyamide monomers with long-chain dicarboxylic acids as end-capping agents; S3: Melt polymerize the polyether soft segment of S1 with the nylon hard segment of S2 to obtain a nylon elastomer; S4: After the nylon elastomer is processed into a film, it is annealed under different temperature gradients, held at the temperature for a certain time, and then slowly cooled to room temperature.

2. The method as described in claim 1, characterized in that, The polyether polyol mentioned in S1 is one or more of polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol; preferably, the number average molecular weight of the polyether polyol is 500-5000 g / mol, more preferably 1000-2000 g / mol.

3. The method as described in claim 1 or 2, characterized in that, The isocyanate S1 is one or more of hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-phenyl diisocyanate, 1,4-phenyl diisocyanate, 2,4-toluene diisocyanate, 2,5-toluene diisocyanate, 2,6-toluene diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate, and 1,5-naphthalene diisocyanate.

4. The method according to any one of claims 1-3, characterized in that, The polydimethylsiloxane described in S1 is a hydroxyl-terminated polydimethylsiloxane with a number-average molecular weight of 500-5000 g / mol, preferably 1000-3000 g / mol.

5. The method according to any one of claims 1-4, characterized in that, S1 includes the following steps: S1-1: Preparation of diisocyanate-terminated blocks by reacting polyether polyols with isocyanates. S1-2: The reaction of diisocyanate-terminated blocks with polydimethylsiloxane.

6. The method as described in claim 5, characterized in that, In S1-1, the molar ratio of polyether polyol to isocyanate is (1:2)-(1:2.05), preferably (1:2)-(1:2.02); in S1-2, the molar ratio of diisocyanate-terminated blocks to polydimethylsiloxane is (2:2)-(2:2.05), preferably (2:2)-(2:2.02).

7. The method according to any one of claims 1-6, characterized in that, The capping agent S2, a long-chain dicarboxylic acid, has the general formula HOOC-(CH2)n-COOH, where n=8-16, and is preferably sebacic acid, dodecadicarboxylic acid, or tetradecanoic acid.

8. The method according to any one of claims 1-7, characterized in that, The polyamide monomer in S2 is selected from one or more of diamines and diacids, lactams, or ω-aminocarboxylic acids; preferably, the diamine is selected from one or more of bis(diamine), decanediamine, dodecanoic diamine, tridecanoic diamine, and tetradecanoic diamine; the diacid is selected from one or more of sebacic acid, dodecanoic dicarboxylic acid, tridecanoic dicarboxylic acid, and tetradecanoic dicarboxylic acid; the lactam is selected from dodecanoic acid lactam; and the ω-aminocarboxylic acid is selected from undecanoic acid.

9. The method according to any one of claims 1-8, characterized in that, The nylon hard segment number-average molecular weight of S2 is 500-8000 g / mol, preferably 1000-3000 g / mol.

10. The method according to any one of claims 1-9, characterized in that, In step S4, the annealing includes the following steps: a first gradient of slowly increasing the temperature from room temperature to 50°C; a second gradient of 50°C-80°C, holding for 2-8 hours; a third gradient of 80°C-100°C, holding for 2-8 hours; a fourth gradient of 100°C-130°C, holding for 2-8 hours; and cooling to room temperature.

Citation Information

Patent Citations

  • A method for synthesizing polyamide-polysiloxane multiblock copolymers

    CN103910845B